Sistema de gerenciamento de liquidez sob a ótica da teoria das restrições: uma adaptação da metodologia Fleuriet - Cia, Joanília Neide de Sales (1998)
The Theory of Constraints (TOC) states that the goal of any company is to make money today and forever. Every system (like a profit-searching company) always has at least one constraint, otherwise it would have unlimited sales and profits. A constraint is any obstacle that limits the system from achieving higher performance towards its goal. Consequently, constraints determine the global performance of the system. So a company can enhance its production of value (i.e. 'earn more money') when it identifies and optimizes the constraint(s) utilization or elevates its capacity. In turn, it will increase sales, throughput, and profit levels. This paper aims to contribute to TOC, answering the following question: 'Are there only physical constraints in the firm, or there might be also financial ones?' In the Brazilian financial market, like most emerging countries, the supply of capital to fund companies' working capital is scarce. This scarcity of capital may impose a constraint on companies' growth and even a threat on their survival. This paper, initially, presents the literature review related to the Theory of Constraints (TOC) and Fleuriet Methodology. From studying these two theories, a liquidity analysis and management model were developed, which show how to measure an eventual financial constraint in comparison to other physical constraints. This model was developed in an MS-Excel Spreadsheet, and the input to it were financial and production data from the CiaCo Textile Mill. It were used both Excel' s data analysis tools and Crystal Ball simulation software. As we can see in the scenario analysis, linear programming, and simulation, the shortgage of an adequate funding to finance company' s activities may be a potential constraint. And whenever the sales growth is greater than the company's ability to raise funding for the new levei of activity, its survival is in jeopardy.